2021
DOI: 10.3390/ijerph182413226
|View full text |Cite
|
Sign up to set email alerts
|

Movement and Physical Activity in Early Childhood Education and Care Policies of Five Nordic Countries

Abstract: The purpose of this study was to examine the values of movement and physical activity (MoPA) using government policy documents (e.g., laws and curricula) on early childhood education and care (ECEC) from Denmark, Finland, Iceland, Norway, and Sweden. This descriptive, comparative study was designed based on curriculum theory and used word count and content analyses to identify similarities and differences in the occurrence of MoPA in the ECEC policies of Nordic countries. Seven terms were identified as MoPA-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 53 publications
(80 reference statements)
0
10
0
Order By: Relevance
“…The educators perceived that MoPA was insufficiently and vaguely mentioned in the curriculum, and they wished for more explicit guidance through the curriculum. MoPA was shown to be of low priority in the ECEC curricula ( Sollerhed et al, 2021 ), which strengthened the educators’ reflections.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The educators perceived that MoPA was insufficiently and vaguely mentioned in the curriculum, and they wished for more explicit guidance through the curriculum. MoPA was shown to be of low priority in the ECEC curricula ( Sollerhed et al, 2021 ), which strengthened the educators’ reflections.…”
Section: Discussionmentioning
confidence: 86%
“…The policy documents regulate ECEC activities and should guide educators in their work. MoPA was shown to be of low priority in the ECEC policies, and the governmental guidance provided to educators and stakeholders therein is inexplicit ( Sollerhed et al, 2021 ), which can increase the impact from the educator’s attitudes, perceived competence and habitus. The importance of educators’ behaviors toward children’s MoPA, including positive or negative prompts and modeling, has been shown to be vital ( Brown et al, 2009b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They preferred to teach more sedentary activities such as language, science or drawing, which is in line with other studies ( 4 ). Findings from a recent study indicated that MoPA, is a low-priority value, to varying degrees, in the ECEC curricula enacted by Nordic countries, especially in Sweden where the guidance provided to educators and stakeholders was inexplicit ( 38 ). The educators seldom or never taught structured MoPA and relied on the children's free play for physical and motor skill development.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades, there has been a development towards more "education" and a more robust political prioritization of formal learning and evaluation in ECEC (8,13,14). Previous research analyzing the values of MoPA using government policy documents (e.g., laws and curricula) on ECEC shows that MoPA in the ECEC policy documents is to varying degrees of a lowpriority value in the Nordic ECEC law documents and guidelines (15). Recently, a Swedish study found limited teaching competencies for MoPA in ECEC teachers and highlighted the need for improved education and competence development ( 16), which has also been found in other countries (17).…”
Section: Introductionmentioning
confidence: 99%